Transformasi Dakwah tentang Hadis-Hadis Hukum di Media Sosial - Herman, M Aras (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The advancement of information technology has significantly transformed Islamic preaching methods, particularly in delivering legal hadiths through social media. Digital da’wah offers easier access to Islamic teachings but also presents serious challenges regarding scholarly authority, hadith validity, and religious literacy among the public. This study examines the transformation of da’wah based on legal hadiths on social platforms, including presentation styles, preacher credibility, and digital community responses. Using a qualitative-descriptive approach and literature review, the findings reveal that digital da’wah must prioritize hadith verification, message contextualization, and synergy between preachers, Islamic institutions, and the public to remain authentic, educational, and relevant to contemporary challenges.